2023
DOI: 10.1002/spy2.312
|View full text |Cite
|
Sign up to set email alerts
|

Explainable artificial intelligence envisioned security mechanism for cyber threat hunting

Abstract: Cyber threat hunting proactively searches for cyber threats, which are undetected by the traditional defense mechanisms. It scans deep to identify malicious programs (ie, malware) that escape from detection. It is important because sophisticated cyber threats can bypass the cyber security mechanisms. The performance of the cyber threat hunting can be improved through artificial intelligence (AI), especially, explainable AI (XAI), which adds trust component to the cyber threat hunting process. Due to the inclus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…When it comes to finding postulations that integrate CTH with a broader cyber security approach, this is far easier said than done. In this regard, Kumar & Chacko (2020) states that while there are models, frameworks and systematic processes developed for CTH, much of the discussions published on these artefacts entail definitions and practical approaches to CTH activities per se. Kumar & Chacko (2020) further observes that there is a lack of propositions that integrate CTH as part of a broader approach.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When it comes to finding postulations that integrate CTH with a broader cyber security approach, this is far easier said than done. In this regard, Kumar & Chacko (2020) states that while there are models, frameworks and systematic processes developed for CTH, much of the discussions published on these artefacts entail definitions and practical approaches to CTH activities per se. Kumar & Chacko (2020) further observes that there is a lack of propositions that integrate CTH as part of a broader approach.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, Kumar & Chacko (2020) states that while there are models, frameworks and systematic processes developed for CTH, much of the discussions published on these artefacts entail definitions and practical approaches to CTH activities per se. Kumar & Chacko (2020) further observes that there is a lack of propositions that integrate CTH as part of a broader approach. This observation confirms our literature review which likewise found a lack of such propositions.…”
Section: Introductionmentioning
confidence: 99%